Enhancing physio biochemical traits and yield of common buckwheat Fagopyrum esculentum with rice husk biochar and nano iron oxide under water stress - Jay Karan Sah; M. A. Mannan; Masuma Akter; Most. Tanjina Akter; Methila Ghosh; Dipanjoli Baral Dola; Usman Zulfiqar; Walid Soufan; P. V. Vara Prasad; Ivica Djalovic (Scientific Reports)
Abstract Climate change is making droughts more frequent, which is a major problem for crop yield, especially for crops that are vulnerable to drought, such as common buckwheat (Fagopyrum esculentum). Drought stress affects negatively on physiological and biochemical processes of plants, leading to reduced yields. This study addresses the knowledge gap regarding effective strategies to mitigate drought-induced damage and enhance productivity in buckwheat. We hypothesized that iron oxide nanoparticles (Fe3O4 NPs) and rice husk biochar could improve drought tolerance in buckwheat by modulating its physiological and biochemical responses. To test this, buckwheat plants were grown under well-watered (80% of field capacity, FC) and drought (40% of FC) conditions following a completely randomized design (CRD) with three replications. Results showed that the application of 50 g/kg rice husk biochar and 400 ppm Fe3O4 NPs, either separately or in combination, significantly enhanced the yield and improved key physiological and biochemical traits, including relative water content, photosynthetic rate, stomatal conductance, chlorophyll content, and antioxidant activity. The combination of Fe3O4 NPs and rice husk biochar led to improvements the plants’ relative water content, photosynthetic rate, chlorophyll levels, membrane stability index, proline, antioxidant activity (DPPH), and seed yield by 22.37, 17.11, 43.05, 16.07, 43.75, 8.59, and 50.87%, respectively compared to untreated drought plants. Moreover, this treatment reduced oxidative stress indicators such as hydrogen peroxide and malondialdehyde by 31.09 and 38.19%, respectively. These results show that Fe3O4 NPs, when combined with rice husk biochar, significantly improve drought tolerance in common buckwheat, providing a viable strategy to increase crop yields in water-limited environments. In view of climate change, this study emphasises the potential of combining biochar with nanomaterials for sustainable agricultural practices.